2017
DOI: 10.3389/fphys.2017.00934
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Silico Risk Assessment in Acquired Long QT Syndrome: The Devil Is in the Details

Abstract: Acquired long QT syndrome, mostly as a result of drug block of the Kv11. 1 potassium channel in the heart, is characterized by delayed cardiac myocyte repolarization, prolongation of the T interval on the ECG, syncope and sudden cardiac death due to the polymorphic ventricular arrhythmia Torsade de Pointes (TdP). In recent years, efforts are underway through the Comprehensive in vitro proarrhythmic assay (CiPA) initiative, to develop better tests for this drug induced arrhythmia based in part on in silico simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
29
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 77 publications
(127 reference statements)
0
29
0
1
Order By: Relevance
“…A recent publication from the Comprehensive in vitro Proarrhythmia assay (CiPA) initiative acknowledged this issue and noted that it is not possible to predict protocol dependence in advance (Fermini et al, 2016). Therefore, if a 'true' IC50 value cannot be reliably determined, then a safety margin is not an effective way of identifying and eliminating risk (Lee et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent publication from the Comprehensive in vitro Proarrhythmia assay (CiPA) initiative acknowledged this issue and noted that it is not possible to predict protocol dependence in advance (Fermini et al, 2016). Therefore, if a 'true' IC50 value cannot be reliably determined, then a safety margin is not an effective way of identifying and eliminating risk (Lee et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…One of CiPA's key objectives is to use detailed in vitro electrophysiological characterization of drug interaction with Kv11.1 to build in silico models to predict arrhythmia risk. One factor that is likely important for this approach, is understanding the state dependence of binding (Lee et al, 2017). It has been shown that for some drugs, the affinity can be as much as 30-fold greater for the inactivated state (Ki) relative to the open state (Ko) (Suessbrich et al, 1997;Ficker et al, 1998;Perrin, Kuchel, et al, 2008;Wu et al, 2015) whereas other drugs have no apparent state preference (Hill et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Lee et al . ). Thus, an important next line of inquiry should be to determine whether this kind of approach can help to assess the kinetics (i.e.…”
mentioning
confidence: 97%
“…Indeed, Lee et al (2017) recently discussed some of the challenges and limitations involved in modelling of the hERG channel and emphasized the need for improved voltage-clamp protocols to characterize drug-channel interaction in in vitro experiments. Furthermore, several recent studies have highlighted the importance of accurately describing statedependence and kinetics of drug binding, instead of relying on steady-state concentration-response curves (Di Veroli et al 2013;Grandi et al 2017;Lee et al 2017). Thus, an important next line of inquiry should be to determine whether this kind of approach can help to assess the kinetics (i.e.…”
mentioning
confidence: 99%